1987
DOI: 10.1107/s0021889887086965
|View full text |Cite
|
Sign up to set email alerts
|

STRUCTURE TIDY– a computer program to standardize crystal structure data

Abstract: A computer program has been written for the purpose of standardizing crystal structure data according to rules formulated by Parthé & Gelato [Acta Cryst. (1984). A40, 169–183]. From input consisting of space‐group symbol, unit‐cell parameters and positional coordinates of the atoms, a reordered and renumbered list of standardized atom coordinates is obtained. The space group is now in the standard setting and the cell is reduced if applicable. The origin and the orientation of the coordinate system have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
977
0
8

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,361 publications
(991 citation statements)
references
References 6 publications
(6 reference statements)
6
977
0
8
Order By: Relevance
“…The atomic coordinates were standardized with STRUCTURE TIDY [23] and are shown in Table 2. Some relevant bond lengths and the anisotropic displacement factors are detailed in Table 3 and M=V, Nb or Ta) [8] and [9] and with the double layer superconducting cooper oxides La 2−x Sr x CaCu 2 O 6 [24].…”
Section: Resultsmentioning
confidence: 99%
“…The atomic coordinates were standardized with STRUCTURE TIDY [23] and are shown in Table 2. Some relevant bond lengths and the anisotropic displacement factors are detailed in Table 3 and M=V, Nb or Ta) [8] and [9] and with the double layer superconducting cooper oxides La 2−x Sr x CaCu 2 O 6 [24].…”
Section: Resultsmentioning
confidence: 99%
“…This manifold of equivalent Wyckoff sequences could have been reduced by standardizing all structures in the ICSD using a program such as STRUCTURE TIDY (Gelato & Parthé, 1987), but then relationships to similar structures in different space groups may have been lost. For example, monoclinic space-group settings like P121/n1 or I12/a1 are transformed to P121/c1 and C12/c1, respectively, even when the monoclinic angles become greater than 120 and the directly discernible similarities of the reported structure to orthorhombic structures is lost.…”
Section: Structure Descriptorsmentioning
confidence: 99%
“…Crystal data of taurine (Sutherland and Young, 1963) were used as initial unit-cell and structural parameters whereas those of Cu 2 CO 3 (OH) 2 (Zigan et al, 1977) and Sr 9 In(PO 4 ) 7 (Belik et al, 2002) reported in the literature were converted by STRUCTURE TIDY (Gelato and Parthé, 1987) into those in conformity with standard settings of monoclinic space groups, i.e. from P2 1 /a to P2 1 /c for Cu 2 CO 3 (OH) 2 and from I2/a to C2/c for Sr 9 In(PO 4 ) 7 .…”
Section: Procedures Of Structure Refinementsmentioning
confidence: 99%